PENERAPAN METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 011 PAGARAN TAPAH DARUSSALAM - Kamusrawati, Kamusrawati (Aksara Public, 2017)
This research is motivated by the low Literacy Starters Grade II SDN 011 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve the Literacy Starters Grade II SDN 011 Pagaran Tapah Darussalam through the implementation of training methods implemented for one month. This research was conducted in SDN 011 Pagaran Tapah Darussalam. Classes that thorough research is a Class II second semester the number of students as many as 11 people. This classroom action research was started at the beginning of February 2015. This form of research is classroom action research. The research instrument consists of instruments teacher and student activity sheets and achievement test. Based on the analysis and discussion before it can be concluded that this study aims to improve the capability of reading starters through training methods Class II graders of SDN 011 Pagaran Tapah Darussalam. This statement can be accepted, because the students' abilities in reading skills beginning to increase. Where dikatehui of the initial data is 62.5 (category competent). The first cycle of the first meeting gained an average of 65.9 (competent enough), the first cycle of the second meeting gained an average of 70.5 (competent), the second cycle of the first meeting gained an average of 77.8 (competent), and the second cycle of meetings both gained an average of 86.9 (competent) with 100% completeness of students or 11 people. Thus, this study was successful.